Asian Monsoon - Wang, Bin. (New York Praxix Publishing, 2006)
Satellite observations and computing technology have advanced our understanding of the monsoon climate enormously in the last two decades. The author provides an update of the knowledge gained over this period, presenting the modern morphology and the physical principles of monsoon climate variation on all time scales ranging from intraseasonal to tectonic time scales. He brings new ideas that can be expected to markedly improve the prediction of monsoon climate, and includes contributions by experts who expand our understanding of the monsoon environment by their study of paleoclimate records, who present evidence of human influences on monsoon climate, and who describe the links of the monsoon to the economy and to human health. This is a comprehensive interdisciplinary text book summarizing new knowledge of Asian monsoon climate variability, dynamics, modeling, and prediction from intraseasonal to geological time scales, and human influence and its links to environmetal/economic issues.
1. Elementary monsoon physics -- 2. Monsoon as coupled atmosphere-ocean-land system -- 3. Global aspects and Asian monsoon circulations systems -- 4. Mean annual cycle of the Asian monsoon -- 5. Severe weather events in Asian monsoon -- 6. Intraseasonal Oscillation -- 7. Interannual variations and ENSO-AM interaction -- 8. Interdecadal variability -- 9. Paleo-monsoon variations -- 10. Numerical modeling and prediction -- 11. Anthropogenic changes -- 12. Monsoon environments -- Appendices: Statistical analysis approaches.
Keywords: Meteorology; Astrophysics; Climatic changes; Ecology; Environmental protection; Geosciences; Meteorology/Climatology.; Extraterrestrial Physics, Space Sciences; Atmospheric Protection/Air Quality Control/Air Pollution; Climate Change; Geoecology/Natural Processes